Image Forces in Physics and Chemistry of Surfaces: Certain Fundamental Aspects - A. M. Gabovich (Хімія, фізика та технологія поверхні)
The occurrence and role of image forces in physics and chemistry of surfaces are analyzed. It is shown that a prima facie simple concept of classical electrostatics has a very complicated background of diverse many-body phenomena. In particular, attention is focused on dynamic effects usually small but, nevertheless, important due to their peculiar manifestations.